Synthesis and Characterization of Polyaniline and Polyaniline - Carbon Nanotubes Nanostructures for Electrochemical Supercapacitors - Kessler, Teresita (2013)
Nanostructures of polyaniline (PANI) and carbon nanotubes (CNT) were synthesized through a simple chemical method of self-organization. An oxidative polymerization process was performed in the monomer (aniline) acid solution with the presence of a surfactant and the addition of multi-walled CNT. The CNT were added with and without pretreatement, CNTf and CNTs respectively. Ammonium persulfate (APS) was used as oxidizing agent and sodium dodecyl sulfate (SDS) as dispersant. Different nanostructures, such as nanoparticles or nanotubes, can be obtained depending on the pretreatment of the CNT. The prepared nanostructures were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), UV-Vis spectroscopy, infrared spectroscopy (FTIR) and electrochemical techniques. Spectroscopy results indicate changes in the adsorption bands depending on the synthetized nanostructures. PANI and PANI composites electrodes were evaluated by cyclic voltammetry (CV) and galvanostatic charge?discharge measurements. PANI-CNTf nanocomposites displayed improved capacitive properties of supercapacitors in H2SO4 electrolyte, namely 1744 F/g at 2 A/g . Moreover, the specific capacitance was strongly dependent on the morphologies of nanoestructures. These characteristics indicate their possible application as supercapacitors materials.